KINERJA IMPLEMENTASI PROGRAM PELATIHAN BERBASIS KOMPETENSI DI UPTD BALAI LATIHAN KERJA KABUPATEN SUMEDANG - Nugraha, Dadan Setia; Subangkit, Ikbal Yanuar; Khoerunisa, Gina Sonia; Apriani, Delis; Setiadiputri, Lesta Bunga; Wahyuni, Bunga Tri (JRPA - Journal of Regional Public Administration, 2024)
This study aims to find out, and obtain objective data and information regarding the Performance of Competency-Based Training Program Implementation at UPTD BLK at the Sumedang Regency Manpower and Transmigration Office. This research uses qualitative methods with a type of descriptive analysis. Informants were determined using purposive sampling techniques so that the informants of this research were the Head of UPTD BLK, UPTD BLK Staff, Sewing Instructors, and Automotive Instructors. Then, data collection techniques are carried out by literature studies, field studies (observation, interviews, and documentation) and triangulation. After that, data processing uses data reduction, data display, data conclucion drawing/verifivation. Performance of Competency Based Training Program Implementation at UPTD BLK at the Sumedang Regency Manpower and Transmigration Office as a whole the program is running quite well, although there are some that need to be improved both from the internal and external environment as a support for the success of this program. With the inhibiting factors for the success of program achievement, employees carry out efforts to minimize the inhibiting factors regarding the ability of training instructors, the falsity of facilities and infrastructure, program target targets, supervision and policies that exist in the implementation of Competency-Based Training Program Implementation Performance at UPTD BLK Sumedang Regency. Based on the results of the study, there are several suggestions, including increasing supervision of competency-based training programs, improving the quality of facilities and infrastructure that support the implementation of training and improving the skills and knowledge of the workforce so that the workforce is better prepared to fill available job vacancies.